Optical, structural and morphological properties of CdS-CdCO$_3$ films. - Chávez Portillo, M.; Sosa Sánchez, A.; Juárez Díaz, G.; A, L.; Cruz Cruz, S.; Gutierrez Pérez, R.; Hernández Téllez, G.; Portillo Moreno, O. (Revista Mexicana de Física, 2015)
CdS-CdCO$_3$ thin films were grown by chemical bath deposition.Different constant deposition temperatures were employed in therange of 20-80$^{°}$C. From X-ray Diffraction (XRD) results can beobserved that intensity of CdS peak is abruptly reduced whendeposition temperature is decreased. By SEM images the formation andchange in shape and size of crystallites can be observed astemperature is decreased. The forbidden energy band gap was 2.4-4.1eV, determined from optical absorption. The formation of productswas further confirmed with FTIR studies.